Synergetic Analysis of Thinking as An attribute of The Human Spiritual World - Muminova Zarifa Odilovna (Peerian Journals Publishing, 2023)
In the article, cognition and thinking is analyzed as a complex social and dynamic system. The definitive essence of cognition is revealed from a synergetic point of view. From a philosophical point of view, the peculiarity of all signs and features of complex dissipative structures to the process of cognition is substantiated. And also knowledge is analyzed as the basis of the essence of man and human civilization. In addition, the constructive and destructive power of cognition is philosophically substantiated.
Keywords: cognition; destructive; structure